2008
DOI: 10.1002/zaac.200800027
|View full text |Cite
|
Sign up to set email alerts
|

Ag4I2SeO4 and Ag3ITeO4 – Two New Silver Solid Electrolytes

Abstract: Two new silver solid electrolytes, Ag 4 I 2 SeO 4 and Ag 3 ITeO 4 , have been synthesized by solid state reactions starting from stoichiometric mixtures of Ag 2 O and AgI with SeO 2 , or TeO 2 , respectively, at elevated oxygen pressures. The new materials have been characterized using powder X-ray diffraction, differential scanning calorimetry, ionic conductivity measurements and single crystal structure determination. Both compounds, Ag 4 I 2 SeO 4 and Ag 3 ITeO 4 , show an abrupt increase in the ionic condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
9
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 22 publications
3
9
0
Order By: Relevance
“…Selected interatomic distances/Å and angles/° for Ag 8 I 2 (CrO 4 ) 3 . Estimated standard deviations are given in parentheses.Cr ( Similar silver coordination numbers and the corresponding bonding distances have been frequently observed in various silveroxide and silveriodine materials [7][8][9][10][11][12][13][14][15][16][17][18]. The shortest Ag-Ag distance observed is 2.880(1) Å (Ag2-Ag2).…”
supporting
confidence: 62%
See 1 more Smart Citation
“…Selected interatomic distances/Å and angles/° for Ag 8 I 2 (CrO 4 ) 3 . Estimated standard deviations are given in parentheses.Cr ( Similar silver coordination numbers and the corresponding bonding distances have been frequently observed in various silveroxide and silveriodine materials [7][8][9][10][11][12][13][14][15][16][17][18]. The shortest Ag-Ag distance observed is 2.880(1) Å (Ag2-Ag2).…”
supporting
confidence: 62%
“…The incorporation of silver ions in an immobile framework of complex oxoanions has proven to be an effective route to raise the silver ion conductivity. Recently, we expanded this field to composites containing AgI and silver selenates and tellurates, this way identifying Ag 3 ITeO 4 , Ag 4 I 2 SeO 4 and Ag 9 I 3 (SeO 4 ) 2 (IO 3 ) 2 as new silver solid electrolytes [17,18]. In the course of our structural investigation of crystalline analogues of the ion-conducting silver iodide silver oxyacid salt glasses, we have synthesized and characterized the compound Ag 8 I 2 (CrO 4 ) 3 .…”
Section: Introductionmentioning
confidence: 99%
“…The crystal structures of quaternary inorganic compounds composed of silver and iodide ions and oxyanionic groups, such as Ag 2 I(NO 3 ) 2 (Birnstock & Britton, 1970), Ag 16 I 12 P 2 O 7 (Garrett et al, 1982), Ag 5 IP 2 O 7 (Adams & Preusser, 1999), Ag 4 IPO 4 (Oleneva et al, 2008), Ag 8 (CrO 4 ) 3 I 2 (Pitzschke et al, 2009b), Ag 9 (GeO 4 ) 2 I (Pitzschke et al, 2009c), Ag 8 I 4 V 2 O 7 (Adams, 1996), Ag 13 (AsO 4 ) 3 I 4 (Pitzschke et al, 2009a), Ag 4 I 2 SeO 4 (Pitzschke et al, 2008a), Ag 3 ITeO 4 (Pitzschke et al, 2008a), Ag 9 I 3 (IO 3 ) 2 (SeO 4 ) 2 (Pitzschke et al, 2008b) and Ag 26 I 18 (WO 4 ) 4 (Chan & Geller, 1977) have been reported.…”
Section: Database Surveymentioning
confidence: 99%
“…Quite a number of compounds of this type were discovered as a result of a detailed search for new silver‐ion electrolytes 19. Among them, those containing silver halogenides compose the most numerous group of compounds with relatively ordered frameworks, Ag 5 I(P 2 O 7 ) 14, Ag 4 I(PO 4 ) 15, and Ag 3 I(TeO 4 ) 17c being the examples. Compounds featuring silver‐telluride frameworks with different topology are known to a lesser extent [16, 20].…”
Section: Introductionmentioning
confidence: 97%